Leolinda Daltro, a caminhante do futuro: uma análise de sua trajetória de catequista a feminista (Rio de Janeiro/Goiás - 1896-1920) - Santos, Paulete Maria Cunha dos (Universidade do Vale do Rio dos Sinos, 2014)
The present thesis aims to analyze the experiences from the educator Leolinda Daltro (c.1859-1935) as a catechist among the indigenous of central Brazil – a region between the Araguaia and Tocantins rivers – and her journey as a mediator and a feminist, after returning to Rio de Janeiro, in the late nineteenth century to the twentieth. As a result of this perception, we chose to effectively provide relief to the impact of the experience of mission Leolinda and its articulation with a wide network of characters (distinguished or not) of regional and national society. For this proposition, we will place here the memory of the individual protagonist understood as one of those cultural practices from records of a "self-production". Leolinda surely felt, thought and lived simultaneous experiences and sometimes disparate – among her political action in defense of indigenous cause and women emancipation – which put her as a witness for multiple spaces and times in the years followed the establishment of the Republic. Related to her journey, we clarify that after we discuss her actions for indigenous cause, we’ll also discourse, even if not deeply, the initial stage of her action in Rio de Janeiro. Action that is seen as crucial to leverage the long course of the movement for women's emancipation, especially in the struggle for political equality between men and women and the full exercise of citizenship.
Keywords: Leolinda Daltro; Trajetória; Mediadora; Causa indígena; Emancipação feminina; Trajectory; Mediator; Indigenous cause; Female emancipation; ACCNPQ::Ciências Humanas::História